Low androgen status inhibits erectile function by increasing pyroptosis in rat corpus cavernosum. (11th March 2021) - Chen, Zhi‐bin; Li, Ge; Lin, Haocheng; Jiang, Jun; Jiang, Rui
Abstract: Background: The mechanism of erectile dysfunction (ED) caused by low androgen status is not fully understood. Objectives: To investigate whether low androgen status inhibits erectile function of rats by inducing pyroptosis in the corpus cavernosum (CC). Materials and methods: Thirty‐six eight‐weeks‐old healthy male Sprague‐Dawley rats were equally divided into six groups: sham‐operated group (4w sham, 8w sham), castration group (4w cast, 8w cast), and castration + testosterone (T) group (4w cast + T, 8w cast + T). The rats in castration + T groups were injected with testosterone propionate subcutaneously every other day. After 4 and 8 weeks, the ratio of maximum intracavernous pressure (ICPmax)/mean arterial pressure (MAP), the level of serum T, the concentration of nitric oxide (NO) and interleukin‐1β (IL‐1β), the expression of NOD‐like receptor pyrin domain containing 3 (NLRP3), apoptosis‐associated speck‐like protein containing a caspase activation and recruitment domain (ASC), Caspase‐1 p20, gasdermin D‐N (GSDMD‐N), transforming growth factor β1 (TGF‐β1), collagen‐I, and collagen‐III, the ratio of smooth muscle/collagen (SM/C), and the proportion of pyroptotic cells in the CC were analyzed. Results: The ratio of ICPmax/MAP (3/5 V) and SM/C, the level of NO and serum T was significantly decreased in castration groups when compared to other groups ( p < 0.01). NLRP3, ASC, Caspase‐1, and GSDMD were mainly expressed in the cytoplasm of smooth muscle cells (SMCs) and endothelial cells (ECs) in the CC. The expression of NLRP3, ASC, Caspase‐1p20, GSDMD‐N, IL‐1β, TGF‐β1, collagen‐I, and collagen‐III was significantly increased in castration groups when compared with other groups ( p < 0.01). The proportion of pyroptotic cells in the CC was increased significantly in castration groups when compared with other groups ( p < 0.05). Discussion and Conclusion: Low androgen status inhibits erectile function of rats by promoting CC fibrosis and reducing NO synthesis through pyroptosis of SMCs and ECs in the CC.